Pharmacy-Mediated Antiplatelet Management Protocol Compared to One-time Platelet Function Testing Prior to Pipeline Embolization of Cerebral Aneurysms: A Propensity Score-Matched Cohort Study. Issue 3 (27th March 2018) - Griessenauer, Christoph J; Jain, Abhi; Enriquez-Marulanda, Alejandro; Gupta, Raghav; Adeeb, Nimer; Moore, Justin M; Grassi, Stacey A; Dalal, Shamsher S; Ogilvy, Christopher S; Thomas, Ajith J; Schirmer, Clemens M
Abstract: BACKGROUND: There is ongoing controversy regarding the optimal antiplatelet regimen, and extent or even need for platelet function testing surrounding Pipeline flow diverter (Medtronic Inc, Dublin, Ireland) embolization of cerebral aneurysms. OBJECTIVE: To compare a unique pharmacy-mediated antiplatelet medication management protocol to a 1-time platelet function testing strategy prior to Pipeline placement. METHODS: A retrospective review of patients with cerebral aneurysms who underwent Pipeline embolization at 2 academic institutions was performed. The first line antiplatelet regimen consisted of aspirin and clopidogrel at both institutions. At institution A, the pharmacy-mediated antiplatelet medication management protocol consisted of repeat platelet function testing using VerifyNow (Accriva Diagnostics, San Diego, California), and dosing adjustments prior to and after Pipeline placement. At institution B, a 1-time platelet function test using light transmission aggregometry was obtained prior to Pipeline placement. Both strategies were compared using propensity score matching. RESULTS: A total of 63 and 165 Pipeline embolization procedures were performed at institutions A and B, respectively. Baseline characteristics differed in aneurysm location and aneurysm maximal diameter. Propensity score matching resulted in 25 matched pairs and demonstrated that the number of procedures in which the patient was switched to an alternative platelet agent was significantly smaller at institution A. There were no differences between the sites with regard to aneurysm occlusion rate, the incidence of thromboembolic and hemorrhagic complications, and modified Rankin scale at last follow-up after propensity score matching. CONCLUSION: Pharmacy-mediated antiplatelet management using VerifyNow is a safe and efficacious alternative to a more traditional approach, and significantly reduces the need to utilize other, potentially more expensive antiplatelet agents.